1994
DOI: 10.1002/1097-0355(199424)15:4<368::aid-imhj2280150406>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and behavior of infants prenatally exposed to drugs: Clinical implications for the mother-infant dyad

Abstract: In trying to prevent developmental delays, we are continually searching for specific events or factors that are responsible for less than optimal development. Recept attention has focused on the effects of cocaine exposure in utero, with the most common effects appearing to be subtle neurobehavioral differences. The purpose of this study was to determine if, at the age of 6 months, infants exposed to cocaine exhibit significant differences in behavior and cognitive abilities. Results of this study revealed dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 17 publications
3
9
1
Order By: Relevance
“…The descriptive analyses showed that the infants who were exposed throughout pregnancy were the most affected; those exposed during the first trimester only were also affected. Although there have been only a few published reports investigating the effects of cocaine exposure on infant temperament, our findings are consistent with those that reported an increase in fussiness and difficultness as a result of prenatal cocaine use [32,58]. The effects of cocaine use on infant temperament may result from the changes in autonomic stability, state regulation, and brain maturation that were found at birth.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The descriptive analyses showed that the infants who were exposed throughout pregnancy were the most affected; those exposed during the first trimester only were also affected. Although there have been only a few published reports investigating the effects of cocaine exposure on infant temperament, our findings are consistent with those that reported an increase in fussiness and difficultness as a result of prenatal cocaine use [32,58]. The effects of cocaine use on infant temperament may result from the changes in autonomic stability, state regulation, and brain maturation that were found at birth.…”
Section: Discussionsupporting
confidence: 91%
“…There have been consistent reports of no detrimental effects of PCE on global cognitive development during infancy, as measured by the Mental Development Index (MDI) of the Bayley Scales of Infant Development (BSID [9] and BSID-II [10]) [4,12,13,20,21,32,36,41,43,48,[58][59][60]65]. Only a few studies have reported detrimental effects on MDI scores.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported the effects of prenatal cocaine exposure on infants’ activity level. However, the findings are largely inconsistent, with some suggesting increases in movement (Mayes et al, 1995, 1996; Struthers & Hansen, 1992) while others suggest a decrease in movement (Alessandri, et al, 1993; Edmondson & Smith, 1994; Martin, et al, 1996). …”
Section: Introductionmentioning
confidence: 98%
“…With the exception of Struthers and Hansen (1992), no studies of CE infants have explicitly examined reactivity and regulation specifically within the motor response system. A number of studies have looked at the activity level (i.e., amount of activity in general) CE infants exhibit (Alessandri et al, 1993; Edmondson & Smith, 1994; Martin et al, 1996; Mayes et al, 1995, 1996; Struthers & Hansen, 1992). However, reactivity of the motor system in response to specific stimuli has not been investigated to date in CE infants.…”
Section: Introductionmentioning
confidence: 99%